2011
DOI: 10.2140/jomms.2011.6.181
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of concrete dams by flat-jack tests and inverse analyses based on proper orthogonal decomposition

Abstract: Dedicated to the memory of Marie-Louise Steele and to Charles Steele.Flat-jack tests have been employed for decades for the assessment of stresses and Young moduli in possibly deteriorated concrete dams and masonry structures. We propose a procedure for such tests that includes several innovations: identification of Young moduli and shear modulus in the presence of orthotropy, of pre-existing normal and shear stresses, and of tensile and compressive strength and fracture energy; use of full-field displacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
0
17
2
Order By: Relevance
“…1 However, it was also pointed out that the magnitude of error function J changes noticeably when the Poisson's ratios change. This is in contrast to the results of Oliveira et al, 3 & Garbowski et al 4 In the following, the obtained results of this study have been outlined in Tables 1-3. For the sake of brevity, all the results are not presented here.…”
Section: Long-term Deterioration: Heterogeneously and Orthotropicallycontrasting
confidence: 91%
See 3 more Smart Citations
“…1 However, it was also pointed out that the magnitude of error function J changes noticeably when the Poisson's ratios change. This is in contrast to the results of Oliveira et al, 3 & Garbowski et al 4 In the following, the obtained results of this study have been outlined in Tables 1-3. For the sake of brevity, all the results are not presented here.…”
Section: Long-term Deterioration: Heterogeneously and Orthotropicallycontrasting
confidence: 91%
“…hydrostatic and gravity loads can provide a dominant state of stresses in the concrete, each of them makes the evolution of the long-term deterioration of the dam to take anisotropic features. After extensive examination of the literatures, the authors 3,4 concluded that probably the only two diagnostic studies conducted on concrete dams considered the degradation of concrete as an anisotropic process. Oliveira & his collaborators 3 performed a modal analysis on the Cabril arch dam located in Portugal using an inverse analysis method for dam material parameter identification.…”
Section: Part I: Transversely Isotropic Elastic Degraded Dammentioning
confidence: 99%
See 2 more Smart Citations
“…Some approaches are based on e.g. optimization of loads (Mróz and Garstecki, 2005), information on natural frequencies (Dems and Mróz, 2001), heat transfer (Ziopaja et al, 2011) or inverse analysis (Garbowski et al, 2011; Knitter-Piątkowska and Garbowski, 2013). Variety of methods are based on comparison of the response of damaged and undamaged structures.…”
Section: Introductionmentioning
confidence: 99%